Paenarthrobacter sp. GOM3 Is a Novel Marine Species With Monoaromatic Degradation Relevance - Rosas-Díaz, Jaime; Escobar-Zepeda, Alejandra; Adaya, Libertad; Rojas-Vargas, Jorge; Cuervo-Amaya, Diego Humberto; Sánchez-Reyes, Ayixon; Pardo-López, Liliana (Frontiers in Microbiology, 2021)
Paenarthrobacter sp. GOM3, a strain that represents a new species-specific context within the genus Paenarthrobacter, is clearly a branched member independent of any group described thus far. This strain was recovered from marine sediments in the Gulf of Mexico, and despite being isolated from a consortium capable of growing with phenanthrene as a sole carbon source, this strain could not grow successfully in the presence of this substrate by itself. We hypothesized that the GOM3 strain could participate in the assimilation of intermediate metabolites for the degradation of aromatic compounds. To date, there are no experimental reports of Paenarthrobacter species that degrade polycyclic aromatic hydrocarbons (PAHs) or their intermediate metabolites. In this work, we report genomic and experimental evidence of metabolic benzoate, gentisate and protocatechuate degradation by Paenarthrobacter sp. GOM3, and gentisate was the preferred substrate with the highest volumetric consumption rate. Genomic analysis revealed that this strain possesses multiple copies for the specific transport of gentisate. Furthermore, analyzing the GOM3 genome, we found five different dioxygenases involved in the activation of aromatic compounds, suggesting its potential for complete remediation of PAH-contaminated sites in combination with strains capable of assimilating the upper PAH degradation pathway. Additionally, this strain was characterized experimentally for its pathogenic potential and in silico for its antimicrobial resistance capability. An overview of the potential ecological role of this strain in the context of other members of this taxonomic clade is also reported.